Duration of Allergen Immunotherapy for Long-Term Efficacy in Allergic Rhinoconjunctivitis - Penagos, Martin (Curr Treat Options Allergy, 2018)
RATIONALE: Subcutaneous and sublingual immunotherapy are effective for allergic rhinitis. An important question is whether allergen immunotherapy provides a sustained clinical effect after treatment cessation. In view of potential side effects, cost and the necessary patient commitment, long-term benefit is an important consideration for the recommendation of immunotherapy over standard pharmacotherapy. PURPOSE OF REVIEW: In this review, we analyse the existing evidence for long-term effects of both routes of administration in the context of double-blind, placebo-controlled, randomised clinical trials that included a follow-up phase of at least 1 year after treatment cessation. RECENT FINDINGS: Overall, evidence suggests that 3 years of either subcutaneous or sublingual immunotherapy result in clinical benefit and immunological changes consistent with allergen-specific tolerance sustained for at least 2–3 years after treatment cessation. SUMMARY: The data presented here support recommendations in international guidelines that both routes of administration should be continued for a minimum of 3 years. Gaps in the evidence remain regarding the long-term efficacy of immunotherapy for perennial rhinitis and studies performed in children.